Pulmonary atrsia with intact ventricular septum. Open heart surgical correction at 32 hours. Issue 5 (May 1977) - Rigby, M L; Silove, E D; Astley, R; Abrams, L D
Abstract : A case of pulmonary atresia with intact ventricular septum is reported in which total surgical correction was carried out successfully at 32 hours of age. Cardiac catheterisation at 17 months has revealed virtually normal haemodynamic and angiographic findings. Surgical correction of this condition in the neonatal period is discussed.